The Impact of Optimism Bias on Strategic Decision-Making and Efficiency in Online Retail Supply Chains - Jialu Li (Systems)
This paper examines the effects of optimism bias within online retail supply chains. Here, optimism refers to a cognitive bias wherein the third-party seller and the e-commerce platform underestimate the likelihood of facing low market potential. The analysis begins by exploring the impacts of each party’s respective biases. The results indicate that while seller optimism generally leads to self-detrimental outcomes, it can also benefit both the platform and the overall system. Conversely, platform optimism does not permanently harm the platform itself but consistently disadvantages the seller and negatively impacts the supply chain. This work then investigates the combined effects of seller and platform optimism on overall system performance, revealing that the entire channel can, in fact, gain from optimism bias. This research offers insights into strategic approaches that may enhance the efficiency of online retail supply chains.